Analysis of kidney injury in intensive care patients diagnosed with COVID-19 using antibiotics (Research, Society and Development, 2022)
The objective of this research was to characterize the profile of patients who developed AKI, analyze laboratory tests, classify according to stages and analyze the adjustment of dosage of antimicrobials. This is a cross-sectional, analytical and retrospective study, whose data collection was carried out with information contained in the MVPEP® Electronic Medical Record System. During the study period, 100 patients were found with confirmed infection for COVID-19, of which 53% developed AKI during ICU stay, which was an average of 13 days. The prevalence of AKI was in male patients with a mean age of 62 years, with Systemic Arterial Hypertension and Diabetes Mellitus of previous comorbidities, with a mortality rate of 67.95%. We observed the presence of hyperkalemia, anemia and increased levels of creatinine and urea in these patients. Another issue analyzed was the use of nephrotoxic antimicrobials, in which polymyxin (83.01%) was the most used, followed by the aminoglycoside class (73,58%). Given the need to adjust antimicrobials, it was analyzed that of the patients who used aminoglycosides, only 26.65% received renal adjustment. According to the data found, we could see that COVID-19 helped in the development of AKI, as we obtained results of a high incidence rate and a large number of deaths, on the other hand, the large use of antibiotics in the course of the disease and the lack of renal adjustment of these can also help in the development of kidney injury.